2005
DOI: 10.1038/modpathol.3800269
|View full text |Cite
|
Sign up to set email alerts
|

Low D2-40 immunoreactivity correlates with lymphatic invasion and nodal metastasis in early-stage squamous cell carcinoma of the uterine cervix

Abstract: Lymphatic invasion and nodal metastasis are predictors of shorter disease-free and overall survival in carcinoma of the uterine cervix. The monoclonal antibody D2-40, which reacts with the oncofetal membrane antigen M2A, is a new selective marker for lymphatic endothelium, and has been shown to be useful in identifying the presence of lymphatic invasion in various malignant neoplasms, including cervical carcinoma. However, the reactivity of the tumor cells with D2-40 has not yet been evaluated. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
80
2
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 32 publications
7
80
2
5
Order By: Relevance
“…The oncofetal M2A antigen expressed in testicular germ cell tumours is identical to podoplanin (Dumoff et al, 2005).…”
Section: Podoplanin Is Upregulated In the Outer Edge Of The Tumour Massmentioning
confidence: 95%
See 1 more Smart Citation
“…The oncofetal M2A antigen expressed in testicular germ cell tumours is identical to podoplanin (Dumoff et al, 2005).…”
Section: Podoplanin Is Upregulated In the Outer Edge Of The Tumour Massmentioning
confidence: 95%
“…Interestingly, focal expression of podoplanin correlated with lymphatic invasion, metastasis and a shorter recurrence-free survival, whereas diffuse expression did not. Hence, podoplanin was proposed as a prognostic marker for cervical cancer (Dumoff et al, 2005(Dumoff et al, , 2006.…”
Section: Cervix Tumoursmentioning
confidence: 99%
“…12,13 It was shown to be a selective marker for lymphatic endothelium allowing the specific identification of lymphatic vessels and the study of lymphatic vessel density in solid tumors. [13][14][15][16][17] We have recently found that cells of cervical squamous cell carcinomas also express podoplanin and characterized the D2-40 immunostaining pattern in a series of tumors treated by radical surgery. 16 We found a highly significant correlation between the level of podoplanin expression and the presence of lymphatic invasion, nodal metastasis, and poor outcome in this cohort of patients with early-stage tumors.…”
mentioning
confidence: 99%
“…1,5 It has been postulated that the density of the lymphatic vessels is a predictor of clinically meaningful outcomes in a number of malignancies. [6][7][8][9][10][11][12][13] One of the most critical steps in the assessment of lymphatic vessel density is the selection of the optimal lymphatic endothelium marker, 1,2,5,[12][13][14][15][16][17][18][19][20][21][22][23] in order to avoid spurious findings arising from the low accuracy of the staining. However, given the absence of a gold standard, the evaluation of the sensitivity and the specificity of the lymphatic endothelium markers is a daunting task.…”
mentioning
confidence: 99%